2023
DOI: 10.3390/vaccines11010134
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antibody-Titer Changes after Second and Third Severe Acute Respiratory Syndrome Coronavirus 2 mRNA Vaccination in Japanese Post-Kidney-Transplant Patients

Abstract: Post-renal-transplant patients have a relatively low antibody-acquisition rate following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccination. In this study, antibody titers were measured 5–6 months and 3 weeks to 3 months after the second and third SARS-CoV-2 mRNA vaccinations, respectively. Post-renal-transplant patients visiting our hospital who had received three SARS-CoV-2 mRNA vaccine doses were included in the study. SARS-CoV-2 immunoglobulin G antibody titers were measured thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The antibody acquisition rate and antibody titer increased with each additional dose, indicating the effectiveness of the additional vaccination. Although we do not present data on neutralizing antibodies in this study, a correlation between anti‐spike antibodies and neutralizing antibodies was shown in a previous report [17]. In our study population, patients with symptoms of SARS‐CoV‐2 infection, such as fever and respiratory symptoms, were excluded, and the results exhibited a strong correlation between anti‐spike antibodies and neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The antibody acquisition rate and antibody titer increased with each additional dose, indicating the effectiveness of the additional vaccination. Although we do not present data on neutralizing antibodies in this study, a correlation between anti‐spike antibodies and neutralizing antibodies was shown in a previous report [17]. In our study population, patients with symptoms of SARS‐CoV‐2 infection, such as fever and respiratory symptoms, were excluded, and the results exhibited a strong correlation between anti‐spike antibodies and neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 52%
“…In univariate analysis, antibody titer was used as a binary variable and factors associated with antibody acquisition were analyzed by the Whitney U test. Factors associated with antibody acquisition were analyzed by multivariate logistic regression analysis with age, gender, BMI, and eGFR as independent variables [16,17]. Statistical significance was set as p < 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous reports have shown low rates of antibody acquisition and antibody production capacity from vaccination in KTRs [ 3 , 41 ]. However, Fujieda et al recently reported that three doses of the SARS-CoV-2 vaccine significantly increased antibody acquisition by 71% in KTRs, suggesting the importance of additional doses in KTRs [ 42 ]. The cohort of KTRs with COVID-19 in the current study had a high overall vaccination rate, with more than 90% of patients receiving 3 or more doses of the vaccine.…”
Section: Discussionmentioning
confidence: 99%